Developing Luminescent Ratiometric Thermometers Based on a Covalent Organic Framework (COF) - Kaczmarek, Anna M.; Liu, Ying‐Ya; Kaczmarek, Mariusz K.; Liu, Hengshuo; Artizzu, Flavia; Carlos, Luís D.; Van Der Voort, Pascal (Angewandte Chemie International Edition, 2020)
Covalent Organic Frameworks (COFs), an emerging class of crystalline porous materials, are proposed as a new type of support for grafting lanthanide ions (Ln3+) and employing these hybrid materials as ratiometric luminescent thermometers. A TpBpy‐COF—prepared from 1,3,5‐triformylphloroglucinol (Tp) and 2,2′‐bipyridine‐5,5′‐diamine (Bpy) grafted with Eu/Tb and Dy acetylacetone (acac) complexes can be successfully used as a luminescent thermometer in the 10–360 K (Eu) and 280–440 K (Tb) ranges with good sensing properties (thermal sensitivity up to 1.403 % K−1, temperature uncertainty δT<1 K above 110 K). For the Eu/Tb systems, we observe an unusual and rarely reported behavior, that is, no thermal quenching of the Tb3+ emission, a result of the absence of ion‐to‐ligand/host energy back‐transfer. The LnCOF materials proposed here could be a new class of materials employed for temperature‐sensing applications following up on the well‐known luminescent metal–organic framework thermometers. A hot candidate: Covalent organic frameworks (COFs) are reported to be an excellent support for the grafting of lanthanide ions/complexes and allow the development of novel types of luminescent thermometers. A unique behavior, that is, no thermal quenching of the Tb3+ emission, is observed in these LnCOF materials.